Facing its Waterloo in diplomacy: Turkey's military in the foreign policy-making process - Ozcan, Gencer (CAMBRIDGE UNIV PRESS, 2009)
The article deals with the decline in the military's influence on the foreign and security policy making process in Turkey. Turkey's harmonization process with the EU that gained momentum in the early 2000s and the US invasion of Iraq in April of 2003 seem to have played a key role in this transformation. While the EU reforms provided for the gradual elimination of legal prerogatives of the military, the increasing US influence in Iraq limited the military's operational power and led to a situation in which it could not exert influence in Northern Iraq, a key area for Turkey's security.
Keywords: Turkey's military; Turkish foreign policy making; Northern Iraq; national security; the US invasion of Iraq; Area Studies; Social Sciences - Other Topics